Language Ecology - Couto, Hildo Honório do (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2017)
Language Ecology v. 1, n. 1, 2017. General Editors: Umberto Ansaldo & Lisa Lim. Amsterdam: John Benjamins Company. ISSN 2452-1949 / E-ISSN 2452-2147, 103p.